ANALYSIS OF NUTRITIONAL AND PSYCHOLOGY FACTORS OF FEEDING DIFFICULTY IN CHILDREN AGED 24-36 MONTHS (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
: Feeding difficulty was a condition where the child is unable to eat and refuses certain foods. Three factors influence the incidence of eating difficulties in children, namely organic factors, nutritional factors, and psychological factors. This study aims to analyze the relationship between nutritional factors and psychological feeding difficulty in children aged 24-36 months. This research was conducted in the area of Tlogosari Wetan Public Health Center with a total sof 8 respondents. This research is in the form of an analytical descriptive study to determine the nutritional and psychological factors of feeding difficulty in children aged 24-36 months. It was found that four children had difficulty eating which led to the classification of inappropriate feeding practice and two children lead to sensory food aversions. Four respondents gave exclusive breastfeeding while two respondents gave breast milk mixed with formula milk. One respondent introduced MPASI at the age of fewer than six months while the other five respondents gave MPASI at the age of six months. All parents have given MPASI according to the guidelines. Some parents have not applied the basic feeding rules properly and correctly. Five respondents did not force the child during the feeding process, while one respondent insisted on feeding when the child had difficulty eating. Difficulty eating can be influenced by the nutritional history of children before solid food, the time and giving of complementary foods as well as children's eating behavior which is a nutritional factor and a psychological factor. The incidence of difficulty eating in children aged 24-36 months leads to the classification of inappropriate feeding practices and sensory food aversions.
Keywords: nutritional factors; psychological factors; exclusive breastfeeding; complementary foods; feeding difficulty